Effects of Incorporation of Ruminally Protected Methionine into a Commercial Mineral Supplement on Growth Performance of Grazing Beef Steers in the Kansas Flint Hills - Rachel R. Donaldson (Kansas Agricultural Experiment Station Research Reports, 2026)
Objective: Our objective was to evaluate the effects of incorporating a ruminally protected methionine hydroxy analog into a mineral supplement on growth performance and mineral intake of grazing beef steers in the Kansas Flint Hills. Study Description: Crossbred beef steers (n = 360) were randomly assigned to one of 18 pastures. Pastures were randomly assigned to one of two mineral treatments: a commercial mineral supplement with no added methionine (NoMet) or a commercial mineral supplement with a methionine hydroxy analog (Met [MetaSmart, Adisseo, Alpharetta, GA]). Steers were grazed for 90 days at a targeted stocking rate of 250 lb of live weight/acre. Mineral was provided for ad libitum intake and body weights were measured on day 0 and day 90. The Bottom Line: Incorporating a methionine hydroxy analog into a commercial mineral supplement did not improve growth performance but did reduce mineral consumption by crossbred beef steers grazing the Kansas Flint Hills.
Keywords: methionine; grazing; performance